BIOAKTIVITAS EKSTRAK DAUN PALA Myristica fragrans SEBAGAI INSEKTISIDA DAN PENGHAMBAT PENELURAN TERHADAP LALAT BUAH Bactrocera carambolae (DIPTERA: TEPHRITIDAE) - , Sandra Bata; , Prof. Dr. Ir. Edhi Martono, M.Sc. ([Yogyakarta] : Universitas Gadjah Mada, 2012)
This research was to determine the insecticidal bioactivity of nutmeg leaves (Myristica fragrans) extract and oviposition deterrent to the fruit flies, Bactrocera carambolae. The study included toxicity bioassays, oviposition deterrent, periode of delay oviposition nutmeg leaves extract, and phytochemic analysis. As the treatments, all bioassays used concentration extract of 100, 50, 25, 12.5, and 6.25%, three replication in each treatment. Recidual effect at each concentrations tested. The mortality of adults infested was observed in 1, 6, 24, 48 hour(s). Oviposition deterrent was presented in non-choiceand in choice test. The number of eggs laid on each treatment was recorded. Period nutmeg leaves extract biossays was carried out in non-choice test. Delay of period nutmeg leaves extract during femalesâ activity to oviposit on each treatment were recorded. Phytochemical biossays of nutmeg leaves extract was by GC-MS analysis in order to determine the components of the compounds existed in the leaves extract. Data were analized using ANOVA and two samples paired t-test. ANOVA was continued by Duncan at significance level of 5% if there was any effect on treatment found. The results showed that extract of nutmeg leaves affected the mortality of Bactrocera carambolae with LC50 3.07% and LC95 28.42%. All netmug-leavesextract concentrations were deterred by fruit files for oviposition with positive ovipostion deterrent indices both in no-and-choice tests. Concentration of 100% and 50% provided a very short delay of oviposition in four days while delay of oviposition at concentration of 25% only lasted in three days after replication, where as at concentration of 12.5 and 6.25% were equal to the control in delay of oviposition period. Thirty-eight compounds was found in netmug leaves extract but that those as insecticides and oviposition deterrent were elemicin and miristicin with 15.12% and 15.93% in concentration, respectively and were higher compared to others compound existed.